Design-based research : Putting a stake in the ground - Barab, Sasha; Squire, Kurt (The journal of the learning sciences, 2004)
The article highlights and problematizes some challenges that are faced in carrying out design-based research. It states that the emerging field of learning sciences is one that is interdisciplinary, drawing on multiple theoretical perspectives and research paradigms so as to build understandings of the nature and conditions of learning, cognition and development. A fundamental assumption of many learning scientists is that cognition is not a thing located within the individual thinker but is a process that is distributed across the knower, the environment in which knowing occurs and the activity in which the learner participates. In other words, learning, cognition, knowing and context are irreducibly co-constituted and cannot be treated as isolated entities or processes.
Keywords: TICE; numérique